Ningmitai capsules have anti-inflammatory and pain-relieving effects in the chronic prostatitis/chronic pelvic pain syndrome mouse model through systemic immunity - Liu, Hanchao; Wang, Zhenqing; Xie, Qigen; Chi, Ani; Li, Yanqing; Dai, Jian; Zhang, Min; Deng, Chunhua; Liu, Guihua (Frontiers in Pharmacology, 2022)
Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) seriously affects the physical and mental health of approximately 90% of males. Due to its complex and unclear etiology, the treatment methods that are currently available for chronic prostatitis/chronic pelvic pain syndrome are controversial, and their efficacy is unsatisfactory. At present, most researchers believe that this kind of prostatitis is caused by autoimmune inflammation. Chinese herbs, which are the essence of traditional Chinese medicine (TCM), are emerging treatment options for inflammation and immune diseases. In this experiment, we investigated the effect of Ningmitai capsules (a kind of traditional Chinese medicine widely used to treat lower urinary tract inflammation and pain in males) on chronic prostatitis/chronic pelvic pain syndrome in a non-obese diabetes-experimental autoimmune prostatitis (NOD-EAP) mouse model. First, by using bioinformatics analysis of data from the Encyclopedia of Traditional Chinese Medicine (ETCM) database, we found that quercetin, which is one of the main components of Ningmitai capsules, could reduce the secretion of CCL2 by inhibiting the MAPK pathway. In animal experiments, it was found that after Ningmitai treatment, the inflammation in mouse prostates was alleviated, the expression of CCL2, which is related to pain, and MAPK pathway components were downregulated, and the activation of the inflammatory NF–κB and STAT3 pathways was reduced. Pelvic pain and inflammation were relieved in mice with EAP. Due to the presence of the blood–prostate barrier, the drug may not completely reach the prostate directly and take effect locally. However, we found that after Ningmitai treatment, the proportions of proinflammatory CD11b+Ly6Chigh immune cells in the spleen, bloodstream (systemic immunity), and prostate (local immunity) were reduced. The infiltration of CD11b+ immune cells into the spleen and prostate was decreased. These findings suggested that Ningmitai can treat chronic prostatitis/chronic pelvic pain syndrome by affecting systemic and local immunities through the CCL2–MAPK pathway.